Genetic Markers For The Diagnosis Of Genital Prolapsed - Yuldasheva D.Yu; Saydakulova D.V (Universitas Muhammadiyah Sidoarjo, 2022)
Prolapse is assumed to be caused by genetically specified alterations in the genital connective tissue. As a result, genetic variables that cause connective tissue pathology take center stage in the quest for genetic predisposition. Collagen proteins are part of the ligaments that ordinarily maintain the pelvic organs and strengthen the muscles involved in pelvic organ prolapse, hence studying their polymorphism in PG is significant